Beyond type 2 cytokines in asthma - new insights from old clinical trials. (3rd May 2020) - Choy, David F.; Arron, Joseph R.
ABSTRACT: Introduction : Human asthma is a heterogeneous disorder on molecular, pathological, and clinical levels. The paradigm of asthma as an allergic process driven by type 2 cytokines and mediators has led to targeted biologic therapies resulting in some clinical benefit in patient subsets. However, some patient subsets and clinical manifestations do not benefit from these interventions, thus redefining unmet needs. Clinical studies of type 2 directed therapies have identified new targets under investigation in clinical development; these include epithelial alarmins, non-type 2 cytokines, cytokine receptor signaling, mast cells and neuroinflammation. Areas covered : We consider lessons learned concerning asthma pathogenesis from observational studies and clinical trials of biologic agents that target type 2 mediators. We also provide a perspective on emerging therapeutic hypotheses to target processes independent of or orthogonal to type 2 inflammation in asthma. Expert opinion : Type 2 inflammation is continuous, not discrete, and is likely a modifier of underlying dysregulated airway physiology. Non-type 2 inflammatory mediators (e.g., IL17, IL6, IFNs), microbiome, alarmins (e.g., TSLP, IL33), mast cells and sensory neurons may represent orthogonal targets to type 2 mediators. There is a need to better match targets and outcome measures in biologically defined patient populations to appropriately test hypotheses in the clinic.